Pembuatan Metil Ester Sulfonat Dari Minyak Sawit (Tahap I : Pembuatan Asam Lemak) - Perpustakaan UGM, i-lib ([Yogyakarta] : Lembaga Penelitian UGM, 2005)
ABSTRAK Anionic surfactant may be produced front palm oil. There are three steps in producing surfactant front palm oil. The first step is saponification process. Secondly is esterification process, and the third is sulfonation process. The research carried out in this project is investigating the first step. In this research, the saponification process was carried out in a 500 mL stirred tank reactor. To obtain the optimal saponification condition, the equivalent ratio of NaOH to CPO was varied from 1 to 1.23. The concentration of caustic soda used was varied from 0.4 to 1 N and temperature was in the range of 40Â°C to 80T. The result shows that the highest CPO conversion was obtained by using NaOH solution of 0.7 N, equivalent ratio of NaOH to CPO of 1:1 at 70 Â°C. Increasing the equivalent ratio of NaOH to CPO at constant concentration of caustic soda (0,7 N) resulted in reducing the CPO conversion, and increasing the ratio of NaOH to CPO simultaneously with increasing the NaOH concentration resulted in increasing the CPO conversion. Keywords: Minyak Sawit dan asam lemak